Gender Translation Gap: The Category of Gender as a Factor in the Transfer of (Post)Yugoslavian Literature into German - Messner, Elena (Przekłady Literatur Słowiańskich, 2022)
The unequal import of (literary) translations of male and female authors from Bosnia, Croatia and Serbia in German will be critically examined in this article regarding the following three aspects: 1. The gender differences in the quantity of translations; 2. The selection strategies for the translation of female authors, especially in the period from 1992 to 2012 (which mostly covers the period of the Yugoslav wars); 3. The role of female actors in the translatory field. The answers to these questions will show whether in this period one could speak of the “gender translation gap”.